11+5(k+1)=3k-(6k-6)

Simple and best practice solution for 11+5(k+1)=3k-(6k-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11+5(k+1)=3k-(6k-6) equation:


Simplifying
11 + 5(k + 1) = 3k + -1(6k + -6)

Reorder the terms:
11 + 5(1 + k) = 3k + -1(6k + -6)
11 + (1 * 5 + k * 5) = 3k + -1(6k + -6)
11 + (5 + 5k) = 3k + -1(6k + -6)

Combine like terms: 11 + 5 = 16
16 + 5k = 3k + -1(6k + -6)

Reorder the terms:
16 + 5k = 3k + -1(-6 + 6k)
16 + 5k = 3k + (-6 * -1 + 6k * -1)
16 + 5k = 3k + (6 + -6k)

Reorder the terms:
16 + 5k = 6 + 3k + -6k

Combine like terms: 3k + -6k = -3k
16 + 5k = 6 + -3k

Solving
16 + 5k = 6 + -3k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '3k' to each side of the equation.
16 + 5k + 3k = 6 + -3k + 3k

Combine like terms: 5k + 3k = 8k
16 + 8k = 6 + -3k + 3k

Combine like terms: -3k + 3k = 0
16 + 8k = 6 + 0
16 + 8k = 6

Add '-16' to each side of the equation.
16 + -16 + 8k = 6 + -16

Combine like terms: 16 + -16 = 0
0 + 8k = 6 + -16
8k = 6 + -16

Combine like terms: 6 + -16 = -10
8k = -10

Divide each side by '8'.
k = -1.25

Simplifying
k = -1.25

See similar equations:

| F(x)=lhx+2 | | 4.2x-2.1=1.68-5.4x | | -26+3x=-36+6x | | 5-3x=7x+5 | | 102=5w+17 | | -9(x-4)=-3x+42 | | 12-2x=2x+8 | | X=8-3(-3) | | A=10x+y+2 | | 21+3x=56 | | -9x-4y=-4 | | -x=-3+2x | | 210p=1890 | | 3x-5=12+3x | | 6n+10=-4n+50 | | 8*n=32 | | 16x^2-27e=0 | | 10=6x+3 | | 9x+11=6x+-9+3 | | 3x-18=12+7x | | 4x-4x+5=12 | | 4+5(x-2)=6+7(x-2) | | (10-2x)(8-2x)(x)=f(x) | | -8+x=4x+1 | | cos+2sec=-3 | | -16=2(1-5x)+4 | | x+3.5=8.5-9x | | 10x-5(x-2)=30 | | 7-4x-3x-5=6x+1+2x-3 | | =(4x-3)(2x+7)-(4x-3)(6-x) | | 3(a+b)+2(a-b)= | | 0.1x+0.25x=20.65 |

Equations solver categories